Respuesta :
Answer:
It is true for all values of x
Step-by-step explanation:
[tex]\frac{(x^2-3x + 2)}{x-1} = x - 2[/tex]
[tex]\frac{(x^2-3x + 2)}{x-1} = x-2[/tex]
First lets simplify Left hand side
LHS = [tex]\frac{(x^2-3x + 2)}{x-1}[/tex]
Solving the numerator of LHS
x² - 2x - x +2
Using factorization to simplify
x(x-2) - 1(x-2)
(x-1)(x-2)
LHS becomes
[tex]\frac{(x-1)(x-2)}{x-1}[/tex]
(x-1) will cancel out
LHS = (x-2)
LHS = RHS
x-2 = x-2
It is evident from the above expression that [tex]\frac{(x^2-3x + 2)}{x-1} = x - 2[/tex] is true for all values of x
Answer:
Yes, it is true for all values of x.
Step-by-step explanation:
We have given the equation:
(x²-3x+2)/(x-1) = x-2
First we solve the nominator L.H.S by factorization method.
x²-3x+2=0
x²-x-2x+2=0
x( x-1)-2( x-1)= 0
(x-1)(x-2)=0
Putting the value of nominator of L.H.S in the equation we get,
(x-1)(x-2)/(x-1)= (x-2)
Simplifying it we get,
(x-2) = (x-2)
Hence, L.H.S = R.H.S
So, it is true for all values of x.